Penerapan Strategi Predict Discuss Explain Observe Discuss Explain (PDEODE) Dalam Penguasaan Konsep Sistem Indera Pada Pembelajaran Biologi di SMA - Tuti Damayanti; Adeng Slamet; Djunaidah Zen (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2017)
This study aims to determine students mastery of concepts  on the material of the sensory system after implementation strategies PDEODE in class XI SMAN 3 Palembang. The population in this study were all students of class XI SMAN 3 Palembang academic year   2015/2016. The research sample is drawn using purposive sampling techniques, in order to obtain class XI MIPA 7 as classrooms sample. The method used is Pre-Experimental Design to design a one- group pretest-posttest design. Data taken the form of student learning outcomes. Data analysis is the t-test, the results of this study showed the average value at KD3.10 class creative. The results of study showed an average increase of 48,03 in order to obtain an index gain of 0,69 with the medium category. T-test results showed that the implementation of the strategy PDEODE significant effect on student learning outcomes XI MIPA 7 SMAN 3 Palembang. Value study of the activity of students in class XI MIPA 7 SMAN 3 Palembang during the implementation of strategies PDEODE in very active category. Keywords: Students activities, mastery of concepts and PDEODE strategy.